The Impact of Transformational Leadership Style on Nurse’s Self-Esteem of Public Hospitals of Lahore Pakistan - Afzal, Muhammad; Waqas, Ali; Farooq, Amina; Hussain, Muhammad (International Journal of Social Sciences and Management, 2016)
Efficient health services require the self-confident and capable medical staff. This milestone cannot be achieved without the flexible and supportive leadership. In the developing countries, health sector has been facing the critical issues like lack of staff, management focus, health facilities and other challenges. Therefore, it is the need of time that supportive and flexible environment should be provided to the nurses so that the self-esteem can be increased and efficient health services can be ensured. Moreover, leaders play a vital role to create the flexible environment that increases the nurse’s self-esteem. Thus, the current study investigates the influence of transformational leadership style on the nurse’s self-esteem of public hospitals of Lahore, Pakistan. The self-administered questionnaire was distributed to 200 nurses of two major public hospitals (Mayo hospital and Jinnah hospital) of Lahore, Pakistan through simple random sampling. The results of the current study reveal that transformational leadership style has significant and positive relationship with nurse’s self-esteem. Therefore, health care sector authorities should adopt the transformational leadership style to enhance the nurse’s self-esteem in their sector to ensure the efficient health care services. Furthermore, limitations and recommendations are given in the last chapter. Int. J. Soc. Sc. Manage. Vol. 3, Issue-4: 287-293